Effects of Sublingual Duster Mite Drops on Lung Function and Exhaled Nitric Oxide in Children with Multiple and Single Allergic Respiratory Diseases. (4th November 2020) - Wang, Li; Ai, Tao; Luo, Ronghua; Fan, Yinghong; Liao, Huiling; Xia, Wanmin; Xie, Cheng; Duan, Yaping; Liu, Yanru
Abstract : Objective . To evaluate the efficiency of sublingual immunotherapy with Dermatophagoides Farinae Drops in children with single and multiple respiratory allergic diseases. Methods . Seventy-one children with allergic respiratory diseases who had been treated with Dermatophagoides Farinae Drops for one year or more were divided into a single allergic group (12 cases) and multiple allergic group (59 cases). The rhinitis score, daytime and night symptom score of asthma, VAS score, drug score, pulmonary function, and FeNO level before and after treatment were evaluated and compared between the two groups. Results . The rhinitis score, night symptom score, VAS score, and drug score in the single allergic group after treatment were significantly lower than those before treatment (p < 0.05 ), but there was no significant difference in the daytime symptom score before and after treatment (p > 0.05 ). The rhinitis score, VAS score, and drug score in the multiple allergic group after treatment were significantly lower than those before treatment (p < 0.05 ), but there was no significant difference in the scores of daytime symptoms and nighttime symptoms before and after treatment (p > 0.05 ). In both the single allergic group and multiple allergic group, the pulmonary function indexes of the patients were significantly improved after treatment, and the FeNO after treatment was significantly lower than that before treatment (p < 0.05 ). There was no significant difference in scores, pulmonary function, and FeNO between the two groups (p > 0.05 ). Conclusion . Sublingual specific immunotherapy is effective in treating multiple and single allergic respiratory diseases in children.